Polish Reception of the German Romance Novel of the 21st Century - POKRYWKA, Rafał (Transfer. Reception Studies, 2016)
Nowadays the romance novel is considered mainly as a genre of mass culture. Only a few attempts to restore the genre in the hierarchy of literary fiction and consequently in the critical reception can be named. This state of affairs is transferred into publishing policies and therefore into the mass reception. Thus, romance novels are either trivialized or revalued by changing or avoiding genre classifications. Prime examples are to find in the Polish reception of the latest German romance novels. Between trivialization (Haas, Glattauer) and revaluation (Streeruwitz, Handke), both of which don't succeed in general reception, there are works which could probably fill a gap between mass and high culture (Stamm, Kumpfmüller), if they were supported by professional criticism. This, as well as lack of translations of many important texts, leads to a general underestimation of the genre.